Penalaran Moral Mahasiswa Ditinjau dari Latar Belakang Pendidikan dan Pendidikan Orang Tua - Ichsan, Ichsan (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2016)
Children are very close to the game. In daily life, children  always do both traditional and modern games.  The game  is something that is considered mandatory as a means of physical motor development  for Early Childhood. The modern game is often played by children in urban areas tend to improve the ability of the brain than muscles.  therefore, the parents who live in urban areas is more advisable to introduce the children to the kinds of games that are more trained strength of their muscles, and traditional games can be one of the solution.The traditional game was slowly but surely becoming obsolete, because it is considered archaic and exhausting. In fact, if evaluated deeper,a variety of traditional games can directly contribute to children such as:1) establishment of a healthy physical, fit, strong, superior and competitive;2) mental development, include: sportsmanship, tolerance, discipline and democratic;3) Theestablishment of moral become more responsive, sensitive, honest and sincere;4) establishment of social skills, are able to compete, cooperate, disciplined, friendly, and nationality.